Artemis Fowl and the time paradox - Colfer, Eoin; Walker, Kev (London : Puffin Books, 2017)
Artemis Fowl, has a new mission - and this time, it's personal. Artemis' mother is dangerously ill, and the only way to find a cure is for Artemis - with Holly Short by his side - to go back in time to battle his younger, more evil self.
800-899
Keywords: Fowl, Artemis (Fictitious character); Leprechauns; Time travel